Prevalence of bovine tuberculosis in slaughtered cattle and factors associated with risk of disease transmission among cattle handlers at Oko-Oba Abattoir, Lagos, Nigeria (2020)
in many developing countries, including Nigeria, where control measures are largely not applied, and the risks of human infection are high. This study was aimed at determining the current prevalence of bTB in slaughtered cattle and identifying factors associated with the risk of disease transmission among cattle handlers toward making informed control measures to limit human-animal interface disease transmission. Materials and Methods: Serum samples at slaughter and lesions suggestive of bTB collected during postmortem examination of 187 slaughtered cattle at the Oko–Oba Abattoir, Agege, Lagos State, Nigeria, were subjected to lateral flow and Ziehl–Neelsen (ZN) techniques, respectively. Furthermore, a structured questionnaire was interviewer-administered to 156 cattle handlers to investigate associated exposure factors to bTB infection. Data were analyzed using bivariate and multivariate logistic regression. Results: The prevalence of bTB in cattle was 25.7% and 7.0% by lateral flow technique and ZN, respectively. The seropositivity was highest in cattle with poor body condition (50.0%), then with good (36.4%) and fair (25.0%) body conditions. The questionnaire survey revealed that being in livestock handling business for >6 years (p=0.001), not knowing the mode of transmission (p=0.02) and ignoring TB lesions at slaughter (p=0.02) were exposure factors associated with increased risk of bTB infection among the cattle handlers. Further, multivariate analysis showed that those who spent more than 6 years in livestock handling were about 4 times (Adjusted odds ratio [AOR]=3.5; 95% confidence interval [CI]=1.1-7.6, p=0.01) more likely to be exposed to bTB infection than those with lesser years. Again, respondents who called the attention of meat inspectors on seeing lesions in animals were about 4 times less likely to be exposed to bTB infection than those who ignored it (AOR=0.3; CI=0.1-0.8, p=0.01). Conclusion: This study has reiterated the endemicity of bTB in cattle population in Nigeria, with the prevalence of 25.7% and 7.0% of bTB by lateral flow and ZN techniques, respectively. This portends potential risk for disease transmission at the human-animal interface, particularly at the abattoir setting. The study also identified important knowledge and practice gaps which would enable informed, all-inclusive, and well-directed programs for effective control of the disease in both human and cattle populations.